Platform Power and Institutional Alignment: Strategic Responses to Regulatory Consolidation in Southeast Asia - Kosidin (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Regulatory consolidation is increasingly reshaping digital platform ecosystems across emerging economies. While intensified regulation is often assumed to constrain dominant platforms, its structural consequences remain under-theorized. This article develops a mechanism-based framework explaining how regulatory consolidation may recalibrate dependence relations and reinforce platform power under specific conditions. Integrating resource dependence theory, institutional response scholarship, and nonmarket strategy perspectives, the analysis conceptualizes consolidation as an institutional inflection point that raises compliance thresholds and stabilizes oversight regimes. When dominant platforms possess strong bottleneck control and developed political capabilities, they are positioned to convert regulatory stabilization into strategic advantage through institutional alignment. Compliance infrastructure becomes a source of relational leverage, while proactive regulatory engagement enhances legitimacy and competitive shielding. However, reinforcement is conditional. Where institutional complexity remains high or structural centrality is weak, consolidation may redistribute influence rather than entrench dominance. By reframing regulatory consolidation as a structurally contingent driver of ecosystem power, this study advances a power-centered understanding of how institutional stabilization interacts with digital market dominance in emerging platform economies.